2009
DOI: 10.1029/2009je003379
|View full text |Cite
|
Sign up to set email alerts
|

Nightside ionosphere of Mars: Modeling the effects of crustal magnetic fields and electron pitch angle distributions on electron impact ionization

Abstract: [1] The night side ionosphere of Mars is known to be highly variable: essentially nonexistent in certain geographic locations, while occasionally nearly as strong as the photoionization-produced dayside ionosphere in others. The factors controlling its structure include thermospheric densities, temperatures and winds, day-night plasma transport, plasma temperatures, current systems, solar particle events, crustal magnetic fields, and electron precipitation, none of which are adequately understood at present. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
140
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(149 citation statements)
references
References 69 publications
9
140
0
Order By: Relevance
“…We try to minimize the impact of this assumption by choosing a dip angle of the magnetic field that matches the dip angle given by the crustal magnetic field model of Cain et al (2003) near 150 km, the altitude of greatest ionization. As recently shown by Lillis et al (2009), strong magnetic gradients can reflect a significant portion of the downward-travelling electrons and can greatly affect the ionization profile. However, if the down-going spectrum is isotropic, the electron flux remains approximately constant with altitude because loss of electrons by magnetic reflection is balanced by the decrease in area of the flux tube through which the electrons travel; only the area upon which the electrons precipitate will decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We try to minimize the impact of this assumption by choosing a dip angle of the magnetic field that matches the dip angle given by the crustal magnetic field model of Cain et al (2003) near 150 km, the altitude of greatest ionization. As recently shown by Lillis et al (2009), strong magnetic gradients can reflect a significant portion of the downward-travelling electrons and can greatly affect the ionization profile. However, if the down-going spectrum is isotropic, the electron flux remains approximately constant with altitude because loss of electrons by magnetic reflection is balanced by the decrease in area of the flux tube through which the electrons travel; only the area upon which the electrons precipitate will decrease.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the down-going spectrum is isotropic, the electron flux remains approximately constant with altitude because loss of electrons by magnetic reflection is balanced by the decrease in area of the flux tube through which the electrons travel; only the area upon which the electrons precipitate will decrease. (However, Lillis et al (2009) showed that, by including altitude dependent scattering effect of the atmosphere, magnetic gradients can also impact the ionization profile due to isotropic distrubutions changing the peak ionization rate by ∼20% between the zero crustal field case and the strongest crustal field gradient they considered.) Brain et al (2006) showed that throughout most of the interval shown in the top panel of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation (the bottom panel of Figure 7) shows this feature occurs at about the same SZA, local time (LT) and latitude for all three cases. The examination of the plots of echo intensity as a function of time and universal time at fixed frequency shows that the altitude of the peak electron density of the ionosphere is at about 160 km, which is the expected height of the ionosphere based on a Monte Carlo Model [Lillis et al, 2009]. At the other times the height of the ionosphere is at about 140 km, which is about 20 km lower than usual, suggesting compression due to solar activity.…”
Section: Datamentioning
confidence: 99%
“…A Monte Carlo transport code was used by Lillis et al [2009], who concluded that the coupled effects of the crustal magnetic field gradients and electron pitch angle distributions on electron impact ionization rates are high enough that they should be included in the modeling of the nightside ionosphere.…”
Section: Introductionmentioning
confidence: 99%